Simulation Method for Frequency Compatibility between LEO Constellation Communication System and Ground IMT Service System - Dong ZHAO; Hong CHEN; Yiang QIN; Hui LI; Wenyue LI (天地一体化信息网络)
In response to the compatibility analysis of frequency sharing between low orbit constellations and IMT systems in recent years, which has caused large-scale differences in time and spatial dimensions between the two systems, a simulation modeling method was proposed that added a mapping relationship between micro and macro systems used spatiotemporal conversion as a means of modeling on the basis of traditional space business system and ground IMT system modeling and simulation.